Aqueous Dispersions of Unmodified Y@C82 (C2v) Endohedral Metallofullerene. Issue 28 (5th October 2017) - Mikheev, Ivan V.; Kareev, Ivan E.; Bubnov, Vyacheslav P.; Volkov, Dmitriy S.; Korobov, Mikhail V.; Proskurnin, Mikhail A.
Abstract: Aqueous dispersions of an unmodified (pristine) (AFD ) nY@C82 (symmetry C2v ) endofullerene were produced with a nearly 100% yield relative to the initial toluene solution of the endofullerene. To the best of our knowledge, this is the first report of this kind of endofullerene aqueous dispersions. The solvent‐exchange ultrasound‐assisted procedure requires no modification of the endofullerene surface or addition of any stabilizing agents into the aqueous phase. The procedure is applicable to any endohedral metallofullerene aqueous dispersions suitable for biomedical applications. The resulting dispersions are stable for at least 6 months. For the produced aqueous dispersions of Y@C82, the zeta potential of ca . –42 mV shows good stability; the average diameter of clusters was as small as ca . 120 nm. Techniques for purification and purity control of nY@C82 and of the intermediate toluene solution of Y@C82 were developed. The residual quantity of organic compounds was less than 1 ppb after the purification. Based on ICP–AES, headspace GC–MS, and MALDI–TOF, a procedure to assess endofullerene concentrations in the aqueous phase was proposed. Abstract : The possibilities of complete transfer Y@C82 ( C 2v ‐isomer) transfer from HPLC‐grade sample to water is shown. For the first time, solvent‐exchange ultrasound‐assisted technique is applied for obtaining aqueous fullerene dispersions of Y@C82 . The stability and concentration parameters of the aqueous dispersions are checked. The technique for estimation and purification of hazardous organic solvent content is developed.